2014
DOI: 10.1002/lt.24033
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of and patient satisfaction with different incision methods for donor hepatectomy in living donor liver transplantation

Abstract: With the decrease in the average donor age and the increase in the proportion of female donors, both donor safety and cosmetic appearance are major concerns for some living donors in living donor liver transplantation (LDLT) because a large abdominal incision is needed that may influence the donor's quality of life. In all, 429 donors who underwent donor hepatectomy for LDLT from April 2010 to February 2013 were included in the study. Donors were divided into 3 groups based on the type of incision: conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(95 citation statements)
references
References 22 publications
3
91
1
Order By: Relevance
“…In the donor procedure, after sufficient mobilization of the liver, sufficiently wide surgical fields are available through the upper hepatectomy (12). In that study, the satisfaction levels of the patients treated with an upper midline incision or transverse incision using laparoscopy were higher and had improved cosmetic outcomes compared to cases treated with a conventional incision (12).…”
Section: Discussionmentioning
confidence: 91%
“…In the donor procedure, after sufficient mobilization of the liver, sufficiently wide surgical fields are available through the upper hepatectomy (12). In that study, the satisfaction levels of the patients treated with an upper midline incision or transverse incision using laparoscopy were higher and had improved cosmetic outcomes compared to cases treated with a conventional incision (12).…”
Section: Discussionmentioning
confidence: 91%
“…Twenty-five articles were reviewed in detail. Finally, 9 non-randomized comparative studies were included for the current meta-analysis[12, 13, 2127]. …”
Section: Resultsmentioning
confidence: 99%
“…This is not special as an upper midline incision is generalized for liver resection. One study has compared a minimal incision and inverted L incision 13. All single OSLR procedures were performed with only an upper midline incision which was a minimal incision for a right hemihepatectomy during major liver resection.…”
Section: Discussionmentioning
confidence: 99%
“…Major liver resection is traditionally performed with an inverted L incision or an inverted T incision. One study has compared minimal open surgery with a previous large incision surgery13 and found that minimal open surgery is feasible for the surgeon and patient.…”
Section: Introductionmentioning
confidence: 99%